Advances in Unsaturated Soil, Seepage, and Environmental Geotechnics 2006
DOI: 10.1061/40860(192)23
|View full text |Cite
|
Sign up to set email alerts
|

The Transient Ground Surface Displacements due to a Point Sink/Heat Source in an Elastic Half-Space

Abstract: Thermoelastic deformation due to a point heat source is the analog of poroelastic response caused by a point sink. In this paper, Biot's three-dimensional consolidation theory is introduced to derive the analytical solutions of the transient consolidation deformation with a point sink in saturated isotropic porous elastic half-space. The transient ground surface displacement produced by a point heat source is described through analog quantities between poroelasticity and thermoelasticity. Closed-form solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Wilson and Gorelick (1996) found that pulsed pumping may cause a greater amount of subsidence as compared with constant pumping rate. Lu and Lin (2005 displayed transient displacements of the pervious half space due to steady pumping rate. Lu and Lin (2005 displayed transient displacements of the pervious half space due to steady pumping rate.…”
Section: The Biot Modelmentioning
confidence: 99%
“…Wilson and Gorelick (1996) found that pulsed pumping may cause a greater amount of subsidence as compared with constant pumping rate. Lu and Lin (2005 displayed transient displacements of the pervious half space due to steady pumping rate. Lu and Lin (2005 displayed transient displacements of the pervious half space due to steady pumping rate.…”
Section: The Biot Modelmentioning
confidence: 99%
“…Assuming the model is decoupled, i.e., the flow field is independent from the displacement field. Considering a point sink of constant strength Q located at point   0, h , the basic governing equations of the elastic saturated aquifer for linear axially symmetric deformation can be expressed in terms of displacements i u and excess pore water pressure p in the cylindrical coordinates   , , r z  as follows (Lu & Lin, 2006: …”
Section: Modeling Simulation and Optimization -Tolerance And Optimalmentioning
confidence: 99%
“…Chen (2002Chen ( , 2005 presented analytical solutions for the steady-state response of displacements and stresses in a half space subjected to a point sink. Lu and Lin (2006) displayed transient ground surface displacement produced by a point heat source/sink through analog quantities between poroelasticity and thermoelasticity. Hou et al (2005) found that pumping induced ground horizontal velocities range from 31 to 54 mm/yr towards azimuths 247° to 273° in the Pingtung Plain of Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that the anisotropic property in the permeability of the soils has significant effects on the excess pore 13 www.intechopen.com water pressure generated by a heat source (Savvidou and Booker, 1989). Lu and Lin (2006) displayed transient ground surface displacement produced by a point heat source/sink through analog quantities between poroelasticity and thermoelasticity. Based on Biot's three-dimensional consolidation theory of porous media, analytical solutions of the transient thermo-consolidation deformation due to a point heat source buried in a saturated isotropic porous elastic half space were presented by Lu and Lin (2007), Lin and Lu (2009).…”
Section: Introductionmentioning
confidence: 99%